The Role Of DSN Fatwa In Realizing Halal Product Guarantees In Indonesia Sharia Economic Review - Lutvi Insana; Azhahira Hafizha Amir; Abdul Halim Nasution (Fox Justi : Jurnal Ilmu Hukum, 2025)
Study This aiming For analyze the role of DSN fatwas in realize guarantee halal products in Indonesia from perspective Islamic economics . The research method used is study studies library , research with technique data collection with method understand and learn theories from various literature like journals , articles , books and reports related . Research results show that the DSN fatwa has role strategic in increase awareness and compliance public to halal products , as well as support developer Indonesian economy . This fatwa also provides positive impact on the economy national through improvement consumption halal products and exports . Therefore that , work The same between government , industry and with society is very important For increase awareness and compliance to halal products .